Energy Consumption and Economic Growth in Newly Industrialised Countries of Asia - Fernandes, Karen; Reddy, Y. V. (International Journal of Energy Economics and Policy, 2020)
The relationship between energy consumption and economic growth has been analyzed by a number of previous studies. However, a consensus has not been reached to define the relationship between the variables. This paper aims to analyze the relationship between energy consumption and economic growth for six Asian countries viz. China, India, Indonesia, Malaysia, Philippines and Thailand by employing statistical and econometric techniques such as ARDL model, Johansen’s Co integration test, VECM, VAR and Toda Yamamoto causality test. Results indicate that energy consumption and economic growth are co integrated in the long run in case of China, India and Indonesia however VECM indicates that both variables are unable to correct itself towards equilibrium after a shock when energy consumption is the independent variable and Real GDP the dependent variable. Co integration does not exist in case of Malaysia, Philippines and Thailand and VAR indicates that GDP is affect by its past values at lag 1 for Malaysia and Thailand and GDP is affected by its past values at lag 1 and 2 for Philippines. In case of India and Thailand there exists a uni-directional causal relationship running from GDP to energy consumption. Keywords: Energy consumption, Economic growth, Co integration, ARDL, Toda Yamamoto Causality. JEL Classifications: P18, Q43 DOI: https://doi.org/10.32479/ijeep.9678